Examining the effects of an interspersed biofeedback training intervention on physiological indices - Ferguson, K. N.; Hall, C.; Divine, A. (The Sport Psychologist, 2020)
The study aimed to determine whether athletes who practice biofeedback are able to self-regulate by reaching resonance frequency and gaining physiological control quicker than if practice time integrates imagery or a rest period. Intervention effectiveness (e.g., intervention length, time spent training) was also explored. Twenty-seven university athletes were assigned to one of three groups: (a) biofeedback (i.e., continuous training), (b) biofeedback/imagery (i.e., interspersed with imagery), and (c) biofeedback/rest (i.e., interspersed with a rest period). Five biofeedback sessions training respiration rate, heart rate variability, and skin conductance were conducted. A repeated-measure analysis of variance showed a significant interaction between groups over time (p = .05) for respiration rate, heart rate variability, and skin conductance, indicating that resonance frequency and physiological control was regained following imagery or a rest period. Postmanipulation check data found intervention length and training time to be sufficient. Combining imagery with biofeedback may optimize management of psychophysiological processes.